MASALAH REFORMASI BIROKRASI - Lili Romli (Jurnal Manajemen Kepegawaian, 2008)
This reformation era, bureucracy in Indonesia are not many change, both in central government or local government. Burecracy behavior at reformation era is resemble with New Orde era. Although central government are many policy about burecracy reform, but burecracy behavior are not many change. Bureucracy in Indonesia still is patrimonialism. For bureucracy reform, both sentral goverment or local goverment, necessary bring into reality good governance. Key words: burecracy, reform, good governance.